Kriteriy diagnostiki dosimptomaticheskoy(premorbidnoy) stadii metabolicheskogo sindroma (Ожирение и метаболизм, 2010)
It is well known that metabolic syndrome (MS) substantially increases the risk of the development of cardiovascular disease, type 2 diabetes and associated mortality. This makes the search of markers of predisposition to MS and predictors of visceral involvement in people with normal body mass an extremely pressing problem, as it is the basis of early prophylaxis. The aim of the research was to determine the early (premorbid) markers of MS. Patients: 458 practically healthy young people aged 18-25. Methods: anthropometric parameters (body mass index, waist circumference), fat component in body composition (FCBC) «BF-306 OMRON» (Japan), lipid (Triglyceride, Total Cholesterol, LDL-Cholesterol, LHL-Cholesterol) and glucose metabolism parameters (Glucose, Immunoreactive insulin, C-peptide, Insulin resistance index HOMA-IR). Results. We found a close correlation of FCBC with glucose (r=0,564-0,427; p=0,01-0,04) and lipid (r=0,547-0,734; p=0,001-0,04) metabolic parameters inherent to MS in young people with normal body mass, which made it possible to consider FCBC as a marker premorbidity of MS (sensitivity - 100%, specificity - 96%). Herein we present an algorithm of diagnostic and tactic activities, which can be used in patients of high risk group for development of MS, including measures of early prophylaxis and preventive therapy.